Investigating the Presence of Strategic Management Accounting Techniques and Their Comparative Study: Bosnia and Herzegovina vs. Anglo-Saxon and European Countries - Lalić, Srđan; Gadžo, Amra; Veledar, Benina (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The study has two research aims. The first aim is to research the presence of individual strategic management accounting techniques in big companies of Bosnia and Herzegovina (BH), while the other research aim is to make a comparative analysis of the presence of individual strategic management accounting techniques in BH to the presence of individual strategic management accounting techniques in chosen European countries: Italy, Czech Republic, Slovenia, Serbia, Croatia and Anglo-Sax countries: Great Britain, The US and Australia. The comparative analysis will enable us to come to a conclusion on similarities and differences in the structure of the presence of individual strategic management accounting techniques, and will be the foundation to outline the conclusions on such state. In realization of the first aim, we collected questionnaire surveys from 110 big companies located in BH, while the other research aim demanded secondary interpretation of previous research data on the presence of strategic management accounting techniques in chosen countries of the world. The results show that the three most represented strategic management accounting techniques in big companies of BH are Quality Costing (52.73%), Strategic Pricing (51.82%) and Benchmarking (50.91%), while the least representing techniques are Life Cycle Costing (11.82%), Attribute Costing and Integrated Performance Management Systems (with 12.73% each) and Activity Based Costing/Management (17.27%).The comparative analysis gives us insight that the most represented strategic management accounting techniques are the ones involved in rival accounting, while in BH the representation of strategic management accounting techniques point at the struggle for existence at the market through the managing the quality and strategic determining selling prices with the corrective actions emerged as result of observation and comparation with competitors.